Intermolecular Interactions in Molecular Ferroelectric Zinc Complexes of Cinchonine - Marko Očić; Lidija Androš Dubraja (Crystals, 2024)
The use of chiral organic ligands as linkers and metal ion nodes with specific coordination geometry is an effective strategy for creating homochiral structures with potential ferroelectric properties. Natural Cinchona alkaloids, e.g., quinine and cinchonine, as compounds with a polar quinuclidine fragment and aromatic quinoline ring, are suitable candidates for the construction of molecular ferroelectrics. In this work, the compounds [CnZnCl3]·MeOH and [CnZnBr3]·MeOH, which crystallize in the ferroelectric polar space group P21, were prepared by reacting the cinchoninium cation (Cn) with zinc(II) chloride or zinc(II) bromide. The structure of [CnZnBr3]·MeOH was determined from single-crystal X-ray diffraction analysis and was isostructural with the previously reported chloride analog [CnZnCl3]·MeOH. The compounds were characterized by infrared spectroscopy, and their thermal stability was determined by thermogravimetric analysis and temperature-modulated powder X-ray diffraction experiments. The intermolecular interactions of the different cinchoninium halogenometalate complexes were evaluated and compared.